KUALITAS SDM DAN LITERASI KEUANGAN PADA UMKM DI ERA DIGITALISASI: SYSTEMATIC LITERATURE REVIEW - Yuniarti, Nur Atika (Jurnal Manajemen dan Profesional, 2024)
This research aims to examine the quality of human resources (HR) and the level of financial literacy in micro, small and medium enterprises (MSMEs) in the era of digitalization through a systematic literature review. The method used is a systematic review of scientific literature published in the last five years. In the era of digitalization, increasing financial literacy is crucial for the sustainability of MSMEs, especially in terms of digital financial management and the use of financial technology. This research also identifies several challenges and opportunities in efforts to improve the quality of human resources and financial literacy of MSMEs in the digital era. These findings provide important implications for policy makers and practitioners in designing effective HR capacity and financial literacy development programs for the MSME sector in the era of digitalization. This literature study shows that the quality of human resources, MSME players are required to be creative and innovative, easily adapt to new technology, have digital skills in various work sectors, and have a high entrepreneurial spirit, as well as being able to deal with automation and artificial intelligence. Meanwhile, financial literacy also has an important role in encouraging the digitalization of MSMEs. MSME players are required to have financial knowledge related to money management, financial knowledge to assess performance periodically, financial behavior in budgeting, and attitudes towards future plans, and financial behavior regarding monthly spending budgets.